Relationship Between Alexithymia and Duration of Internet Use - Yosep, Iyus; Wardani, Rachmawati Kusuma; Sismayadi, Zahrul Insan; Mardhiyah, Ai (Indonesian Journal of Global Health Research, 2024)
One of the problems faced by nursing students is alexithymia, alexithymia is an emotion that can appear unintentionally, but there is a state of emotional processing deficit that causes a person to be unable to express his emotions or known as alexithymia. Internet use in Indonesia, which reaches 160 million people, has a link between addiction to internet use and the incidence of alexithymia. Objective: This study aims to find out the relationship between alexithymia and duration of internet use at the Faculty of Nursing, Universitas Padjadjaran. Method: The research population is active students of the Faculty of Nursing Universitas Padjadjaran. This type of research is quantitative with a descriptive correlation design. The sampling technique to be used is total sampling (n=590). The instrument in this study used an instrument, namely the Toronto Alexithymia Scale-20 (TAS-20). Data analysis used univariate and bivariate analysis. Bivariate analysis used spearman test. Results: The results of data analysis obtained sig. 0.045 < 0.05 with a positive correlation coefficient of 0.083, which means the strength of the relationship is weak. Individuals who experience depression and bullying can change their emotions for the better when using the internet and text messages than using drugs illegally and the internet is easy to access and easy to use. Research shows that the higher the level of internet or social media addiction, the higher the alexithymia score. Conclusion: There is a weak and positive relationship between alexithymia and duration of internet use at the Faculty of Nursing Universitas Padjadjaran.